The Adjustment Process Lonto Leok Student Groups at Muhammadiyah University of Sidoarjo: Proses Penyesuaian Diri Kelompok Mahasiswa Lonto Leok di Universitas Muhammadiyah Sidoarjo - Pratama, Ifanda Ilham; Sufyanto, Sufyanto (Journal of Islamic and Muhammadiyah Studies, 2022)
This study aims to provide information on how to adjust to the Lonto Leok student group and also to find out what factors hindered them in their efforts to adjust while studying at Muhammadiyah University of Sidoarjo. The method used in this study is a qualitative descriptive approach, The technique of determining the informants used purposive sampling, and data collection was carried out by means of interviews, observation and documentation. The results of this study reveal that in an effort to adjust to Sidoarjo, there are different ways, such as increasing friends, being active in organizations, smiling, being yourself, not being easily carried away by feelings and respecting all differences. In addition to this method, all informants in this study found factors that hindered self-adjustment, these factors were physical factors, development and maturity, psychological, environmental and cultural and religious factors. In addition, language difficulties became the main problem, they found difficulties in the realm of language, all informants also wanted to learn Javanese to make it easier for them in their daily lives. As well as peer support also helps informants in launching their adjustment efforts while on campus.